Morphological Studies and Quality Evaluation of Turmeric Types - Joseph Philip (Department of Horticulture (Plantation Crops), College of Horticulture, 1978)
A study using 19 turmeric types was conducted during the period from April 1977 to June 1978 at the College of Horticulture, Vellanikkara with a view to find out the possibility of distinguishing different types based on morphological parameters, to screen out the types with high yield and quality, to evaluate their relative susceptibility or tolerance to important pests and diseases and to study the yield and quality variations at different periods of maturity. The study revealed that morphological characters are not reliable to classify the turmeric types, although some of them can be distinguished by rhizome characters. The morphological characters such as the height of plant, length and breadth of leaf, leaf area index, petiole length, number of leaves per tiller, number of roots per plant, length of root, length of primary fingers and girth of mother rhizome were positively correlated with yield, whereas the intensity of shoot borer attack was negatively correlated with yield. All the types were susceptible to the incidence of ‘leaf spot’, ‘leaf blotch’ and shoot borer infection. The type VK5 (Mannuthy Local) showed the minimum incidence of pest and diseases. The yield of turmeric showed significant variation among the types. Maximum yield of green turmeric was noticed in the type VKI (Chayapasupa) whereas the type VK5 (Mannuthy Local) recorded the maximum yield of cured produce. Significant variation was noticed among the types with regards to the oleoresin and curcumin content. The oleoresin content varied between 12.1 and 21.1 per cent and the variation in curcumin content was from 2.33 to 6.55 per cent. The uncured turmeric samples had a higher content of oleoresin and curcumin than that of cured samples. The yield, percentage recovery of dry produce, oleoresin and curcumin varied significantly among the different periods of maturity in case of the types VK4 (G.L.Puram-II), VK5 (Mannuthy Local), VK17 (Armoor Cll-324) and VKII (Vontimitta). The dry yield, curcumin and oleoresin per hectare were maximum on 270th day whereas the maximum percentage recovery of oleoresin was on 180th and 270th day after planting. The types VK5 (Mannuthy Local), VK1 (Chayapasupa), VK2 (Kuchupudi) and VK3 (Kodur) can be recommended for large scale cultivation in the plains of Kerala as these types are found to be superior in yield of dry produce, oleoresin and curcumin per hectare. Of these VK5 (Mannuthy Local) and VKl (Chayapasupa) are preferred because of the low incidence of pest and diseases. The optimum time of harvesting turmeric is found to be on 270th day after planting under Vellanikkara conditions.